Prophylactic Antioxidant Potential of Gallic Acid in Murine Model of Sepsis - Harikesh Maurya; Vaishali Mangal; Sanjay Gandhi; Kathiresan Prabhu; Kathiresan Ponnudurai (International Journal of Inflammation)
Present study is to investigate the effect of Gallic acid pretreatment on survival of septic animals and oxidative stress in different organs like lungs, liver, kidney, spleen, and vascular dysfunction of mice. Sepsis was induced by cecal ligation and puncture (CLP) in healthy adult male albino mice (25–30 g) and was divided into 3 groups each consisting of 6 animals, that is, sham-operated (SO group (Group I), SO + sepsis (Group II), and Gallic acid + sepsis (Group III)). Group III animals were pretreated with Gallic acid at the dose rate of 20 mg/kg body weight for 2 days before induction of sepsis. Animals were sacrificed on 8th day and the tissue samples were obtained for further investigation on lipid peroxidation (LPO), malondialdehyde (MDA), superoxide dismutase (SOD), catalase (CAT), and glutathione reductase (GSH). Gallic acid pretreatment significant (P<0.05) reduces kidney, spleen, liver, and lungs’ malondialdehyde level in septic mice. However, it fails to improve reduced glutathione level in all given organs, while, Gallic acid pretreated mice showed significant improvement in SOD activity of kidney and spleen when compared to septic mice. Finally, the beneficial effects of Gallic acid pretreatment in sepsis are evident from the observations that Gallic acid partially restored SOD and catalase activity and completely reversed lipid peroxidation. Further studies are required to find out the possible mechanisms underlying the beneficial effects of Gallic acid on large population.